A WORKSHOP COURSE TO RECONCILE KNOW-HOW AND KNOWLEDGE IN THE FIELD OF TECHNOLOGY (CASE OF LEBANESE HIGHER EDUCATION) - Marie-Thérèse, Saliba (European Scientific Journal, ESJ, 2015)
This action research addresses issues related to the skills in higher education in order to provide transferable skills and employability in engineering and technological fields. This research aims to offer a practical guide to effectively integrate skills into first year engineering courses. It is in this spirit, and in the context of Lebanese Universities that we conducted a reflection and an experiment around the design of a learning environment project (Project Approach) as a solution to the fragmentation of subjects in science and technology. We report in this article the problems observed in teaching in Lebanon before presenting our solution (Project Approach), its foundations and put it into practice around the creation of a robot. This study was conducted with 80 first year electrical engineering and computer science students at a Lebanese university.